2019
DOI: 10.3390/pharmaceutics11070334
|View full text |Cite
|
Sign up to set email alerts
|

Towards Printed Pediatric Medicines in Hospital Pharmacies: Comparison of 2D and 3D-Printed Orodispersible Warfarin Films with Conventional Oral Powders in Unit Dose Sachets

Abstract: To date, the lack of age-appropriate medicines for many indications results in dose manipulation of commercially available dosage forms, commonly resulting in inaccurate doses. Various printing technologies have recently been explored in the pharmaceutical field due to the flexible and precise nature of the techniques. The aim of this study was, therefore, to compare the currently used method to produce patient-tailored warfarin doses at HUS Pharmacy in Finland with two innovative printing techniques. Dosage f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 57 publications
1
61
0
3
Order By: Relevance
“…Investigations into novel oral dosage forms for children have indicated that formulations such as orodispersible mini-tablets or films are promising options in pediatric drug development, enabling personalized and flexible drug administration [7,32]. Dose titrations of enalapril maleate doses in the range of 0.025-4 mg were manageable with orodispersible mini-tablets of two different strengths (0.25 and 1 mg, respectively), facilitating flexible dosing for different patient groups [32].…”
Section: Main Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…Investigations into novel oral dosage forms for children have indicated that formulations such as orodispersible mini-tablets or films are promising options in pediatric drug development, enabling personalized and flexible drug administration [7,32]. Dose titrations of enalapril maleate doses in the range of 0.025-4 mg were manageable with orodispersible mini-tablets of two different strengths (0.25 and 1 mg, respectively), facilitating flexible dosing for different patient groups [32].…”
Section: Main Findingsmentioning
confidence: 99%
“…The production of orodispersible films by means of 2D or 3D printing is considered a possibility for on-demand manufacturing of patient-specific doses [33,34]. Recently, two different printing technologies were used to produce orodispersible films containing four different commonly used pediatric doses of warfarin sodium [7]. It was shown that content uniformity and dose accuracy of the printed orodispersible films were at least equally good as for dose powders currently used for pediatrics.…”
Section: Main Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to provide additional information about the dosage form and to reduce the errors that occur in the administration of medication a Quick Response (QR) code was printed onto the ODFs using IJP. The study demonstrated how printing technologies are promising techniques for the development of patient-specific dosage forms [19].…”
Section: Semisolid Extrusion Printing (Ext) and Inkjet Printing (Ijp)mentioning
confidence: 96%